2022
DOI: 10.3390/cancers14102541
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Characterization of Intratumoral Autonomic Innervation in 32 Cancer Types in the Cancer Genome Atlas

Abstract: Over the past two decades, multiple studies have demonstrated the important role that the autonomic nervous system (ANS) plays in tumorigenesis and cancer progression. However, the mechanisms by which this process occurs have only recently begun to be elucidated. Further, the extent of autonomic innervation in various cancer types and its effects on tumor molecular, immunological, and histopathological features, as well as on patient outcomes, are not yet fully characterized. In this study, we analyzed intratu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…After controlling for age, BMI, KPS and tumor stage, low HF‐HRV predicted poor HRQoL in BC patients. Recently, it has been found that ANS in tumors is usually associated with angiogenesis and immunosuppression in the tumor microenvironment, thus participating in the development and progression of cancer 40 . An animal experiment showed that there are nerve fibers embedded in BC masses, and the ANS has a direct influence on tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…After controlling for age, BMI, KPS and tumor stage, low HF‐HRV predicted poor HRQoL in BC patients. Recently, it has been found that ANS in tumors is usually associated with angiogenesis and immunosuppression in the tumor microenvironment, thus participating in the development and progression of cancer 40 . An animal experiment showed that there are nerve fibers embedded in BC masses, and the ANS has a direct influence on tumor growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic nervous system (ANS) signatures are validated using marker genes 19 . Differentially expressed genes (DEGs) among GPL subtypes are determined using the “limma” R package with FC >1.4 and FDR <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…-3 of 16 2.3 | Nerves signatures, pathways and immune microenvironment assessment Autonomic nervous system (ANS) signatures are validated using marker genes. 19 Differentially expressed genes (DEGs) among GPL subtypes are determined using the "limma" R package with FC >1.4 and FDR <0.05. GC driver genes (Table S2) and nerve-cancer related genes (Table S3) were used to obtain differentially expressed driver-related and nerve-regulated genes.…”
Section: Immunohistochemistry and Digital Quantification Of Nerves De...mentioning
confidence: 99%
“…Mounting evidence has indicated that the nervous system plays an essential role in cancer progression. Tumour cells release various neurotrophic factors to promote their own innervation 1–3 . In turn, infiltrating nerves also mediate various malignant biological processes of the tumour 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Tumour cells release various neurotrophic factors to promote their own innervation. [1][2][3] In turn, infiltrating nerves also mediate various malignant biological processes of the tumour. 4 Such discoveries make identification of predictive markers and mechanisms of cancer neuroscience an area of emerging research.Most reports about the interactions between solid tumours and the nervous system have described perineural invasion (PNI).…”
mentioning
confidence: 99%